Volar Plate Draping (VPD) for Severely Comminuted Proximal Phalanx Head Fractures - Ashwini Varadha Rajan; Vigneswaran Varadharajan; Praveen Bhardwaj; S. Raja Sabapathy (Indian Journal of Plastic Surgery)
While proximal phalangeal joint injuries with comminution of the base of the middle phalanx are common injuries, proximal interphalangeal (PIP) joint fracture dislocations with an intact base of middle phalanx and a comminuted head of proximal phalanx are rare. Volar plate arthroplasty and other described techniques prevail for the former injury, while the latter does not have any supportive literature on the exact method of management. We herein present a 20-year-old male with a severely comminuted head of proximal phalanx fracture with dislocation of the PIP joint, which was not reconstructable but was managed successfully with a novel technique of volar plate draping that resurfaced the raw phalangeal head. A 3-year follow-up of the patient, whose finger has full, painless, and complete functional range of movement, gives us the belief that this procedure can provide a fully functional finger where other methods fail to do so.